Trends of primary and subsequent cancers of the gastrointestinal tract in the Czech population, 1976-2005 - Dítě, Petr; Geryk, Edvard (Digestive diseases (Basel, Switzerland), 2010)
A total of 355,624 new gastrointestinal (GI) cancers were registered in 1976-2005 in the Czech Cancer Registry. Of these, there were 14,744 (4.1%) primary and 26,790 (7.5%) subsequent cases, of which all were GI multiple cancers (12.1% males and 11.1% females). The primary GI cancers were followed by 16,362 other neoplasms (60.7% males, 39.3% females); the subsequent GI cancers were preceded by 31,519 other neoplasms (55.8% males, 44.2% females). Double neoplasms were higher in females, and multiple cases were higher in males. The number of primary cases peaked in 1997, the number of subsequent cases increased until 2005. Almost half of the cases were registered in the age group of 50-69 years. The average interval between primary GI cancers and subsequent neoplasms was 6.1 years; the ratio of synchronous to metachronous cases was 1:3.6 in males and 1:5 in females. The most frequent synchronous cases in males were cancers of other GI, urinary, genital and respiratory tract; in females these were cancers of other GI, genital and urinary tract and the breast. The most frequent cancers preceding the next subsequent GI cancer included primary cancers of the skin, other GI, genital, urinary and respiratory tract for males, and those of the skin, genital and other GI tract and breast cancer for females. The 23,462 subsequent GI cancers reported as a 2nd cancer included early stages in 29.6% of males and 27.9% of females, advanced stages in 31.2% males and 31.3% females, and unknown stages in 39.3% males and 40.8% females. Of 3,562 primary neoplasms of advanced stages before subsequent GI cancers, 2,093 were cases at stage III (51.4% males, 48.6% females) and 1,469 cases were at stage IV (60.2% males, 39.8% females); the most frequent in males were primary cancers of other GI, respiratory and genital tract, and cancers of other GI, breast and genital cancers in females. Of 9,568 primary neoplasms before subsequent GI cancers at advantage stages, 3,325 cases were registered before stage III (53.9% males, 46.1% females) and 6,243 cases before stage IV (57.7% males, 42.3% females). The most frequent in males were primary cancers of skin, other GI, genital and urinary tract; for women, the most frequent were those of the skin, genital cancers, breast and other GI tract. Up to October 2007, 78.2% males died and 21.8% survived primary GI cancers; for women, 76.6% of died and 23.4% survived. Of the subsequent GI cancers, 86.7% males died and 13.3% survived; for women, 85.7% died and 14.3% survived.
Keywords: Gastrointestinal Neoplasms; Male; zeměpis; Neoplasm Staging; Česká republika; gastrointestinální nádory; staging nádorů; mnohočetné primární nádory; mužské pohlaví; incidence; Geography; Czech Republic; Neoplasms, Multiple Primary; lidé; ženské pohlaví; Humans; Age Distribution; věkové rozložení; Female; Incidence